2015
DOI: 10.1016/j.cell.2015.07.048
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Control of Chromatin States in Humans Involves Local and Distal Chromosomal Interactions

Abstract: SUMMARY Deciphering the impact of genetic variants on gene regulation is fundamental to understanding human disease. Although gene regulation often involves long-range interactions, it is unknown to what extent non-coding genetic variants influence distal molecular phenotypes. Here, we integrate chromatin profiling for three histone marks in lymphoblastoid cell lines (LCLs) from 75 sequenced individuals with LCL-specific Hi-C and ChIA-PET-based chromatin contact maps to uncover one of the largest collections o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
375
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 315 publications
(404 citation statements)
references
References 40 publications
28
375
0
1
Order By: Relevance
“…In line with this, gene silencing on the inactive X chromosome in female mammalian cells was shown to also occur at the level of TADs, and gene clusters of escapees that do not become silenced correlate with TADs (Marks et al 2015). Further strong evidence for TADs being the functional units of the genome came from two recent studies that established the existence of the long-range impact of genetic variation on histone modifications elsewhere on chromosomes: Both studies showed that such communication takes place in the context of TADs (Grubert et al 2015;Waszak et al 2015). TADs are formed during early G1 of the cell cycle, concomitant with the establishment of the replication timing program (Dileep et al 2015), and TAD boundaries often coincide with replication domain boundaries (Pope et al 2014).…”
Section: Tads and Sub-tadsmentioning
confidence: 96%
“…In line with this, gene silencing on the inactive X chromosome in female mammalian cells was shown to also occur at the level of TADs, and gene clusters of escapees that do not become silenced correlate with TADs (Marks et al 2015). Further strong evidence for TADs being the functional units of the genome came from two recent studies that established the existence of the long-range impact of genetic variation on histone modifications elsewhere on chromosomes: Both studies showed that such communication takes place in the context of TADs (Grubert et al 2015;Waszak et al 2015). TADs are formed during early G1 of the cell cycle, concomitant with the establishment of the replication timing program (Dileep et al 2015), and TAD boundaries often coincide with replication domain boundaries (Pope et al 2014).…”
Section: Tads and Sub-tadsmentioning
confidence: 96%
“…Genomewide association studies showed several events of single nucleotide variants (SNVs) occurring at enhancers of disease-causing genes. 114,115 Using the knowledge revealed so far about the role of SNVs or mutations in gene deregulation and disease susceptibility, it could be hypothesized that such alterations may be causative for low CEBPA expression in these CEBPA low AML subgroups. The application of DNA custom capture sequencing in large AML cohorts would be a potential tool to reveal mutations or SNVs that may be occurring in the CEBPA locus.…”
Section: Hijacking Of the Cebpa Locus By Potential Oncoproteinsmentioning
confidence: 99%
“…One of the most widely used methods to detect higherorder chromatin structure is the chromosome conformation capture (3C) family of techniques. 146,153,160 Chromatin immunoprecipitation sequencing (ChIP-seq), micrococcal nuclease sequencing (MNase-seq), and chromatin immunoprecipitation exonuclease (ChIP-exo) methodologies provide information over the »1-150 bp length scale, allowing for analysis of nucleosome fiber folding 149,[161][162][163][164] . While these types of approaches provide information on populations of cells, single-cell approaches have now become feasible.…”
Section: Does Nuclear Morphology Affect Chromatin Organization?mentioning
confidence: 99%